Combined clinoptilolite and Fe(O)OH for efficient removal of Cu(II) and Pb(II) with enhanced solid–liquid separation - Jennifer N. Enemmoh; David Harbottle; Muhammad Yusuf; Timothy N. Hunter (Discover Chemical Engineering)
Abstract This study investigated combining fine clinoptilolite with iron hydroxide coagulant, as a cost-effective, dual-purpose flocculant for enhanced removal of Pb2⁺ or Cu2⁺ ions, along with the solid–liquid separation and physicochemical analysis. For the clinoptilolite, adsorption kinetics fitted a pseudo-second-order (PSO) rate model with higher rate constants for Pb2+, while equilibrium adsorption data fitted the Langmuir monolayer model, with Q max similar at 18.8 mg/g for Pb2+ and 18.3 mg/g Cu2+. TEM elemental mapping of the clinoptilolite evidenced areas of K and Fe impurities, while SEM suggested a uniform distribution of aggregates comprising a clinoptilolite core with decorated FeOOH. X-ray diffraction (XRD) indicated the FeOOH phase as α-FeOOH (Goethite) with no change in structure on inclusion of adsorbed Pb2+. Combined clinoptilolite-FeOOH flocs were significantly larger than FeOOH only precipitates, while flocs formed from 0.5 wt% FeOOH and 1 wt% clinoptilolite produced the fastest settling rates and greatest consolidation. Compressive yield stress data also correlated with enhanced dewatering of the combined systems, due to the dense clinoptilolite acting as a weighter material. For final metals removal, combined flocs outperformed FeOOH across a broad concentration range, achieving > 98% removal for both Pb2⁺ or Cu2⁺. The greater metals removal combined with denser floc production and improved settling features highlights significantly enhanced performance above that possible from either ion exchange or precipitation alone. Graphical abstract